DESIGNING A SUSTAINABILITY REPORTING FRAMEWORK FOR INDONESIAN LOCAL GOVERNMENTS THROUGH STANDARD HARMONIZATION AND STAKEHOLDER VALIDATION - Mutia, Khafia; Darwanis, Darwanis; Rahmawaty, Rahmawaty; Fahlevi, Heru (JRAK, 2026)
Local governments face growing demands for sustainability disclosure, yet the absence of a sustainability framework for local governments limits accountability and effective use of sustainability information. This study develops a conceptual sustainability reporting (SR) framework for Indonesian local governments. The framework was constructed in three stages. First, internationally recognized standards and guidelines, the Sustainability Accounting Standards Board (SASB), Global Reporting Initiative (GRI), INTOSAI Working Group on Environmental Auditing (WGEA), and Indonesia’s Sustainable Development Goals (SDGs), were systematically mapped and synthesized. Second, the integrated elements were structured into a framework aligned with public-sector governance and accountability requirements. Third, the framework was validated and refined through stakeholder feedback collected via online questionnaires from 20 key public-sector respondents. The resulting framework offers a structured reporting architecture that incorporates legal, governance, and local government dimensions. This study contributes a practical reference for policymakers and auditors while advancing SR research in decentralized public-sector contexts.